Electromagnetic diffraction by metal cylinder coated with inhomogeneous magnetoactive plasma sheath.I - Azarenkov, N.A.; Galaydych, V.K. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2008)
This paper is devoted to the problem of diffraction of low frequency electromagnetic waves incident from a homogeneous magnetoactive plasma by a metal circular cylinder surrounded by radially inhomogeneous plasma sheath. The external magnetic field is parallel to a cylinder axis; the wavevector of incident plane wave is perpendicular to this axis. It is assumed that plasma is cold and perturbations in it are governed by Maxwell’s and two-liquid hydrodynamic equations. The exact solutions for fields in both linear and power plasma sheath profile are obtained. The cross-sections for backward and forward scattering as a function of incident wave vector are derived for various parameters of task. The dependences of these cross-sections upon these parameters are analyzed. The inhomogeneous plasma sheath enhances the oscillation amplitude of the back scattering cross-section and changes in several times the value of the forward scattering cross-section. В данной работе решена задача дифракции низкочастотной электромагнитной волны, падающей из однородной магнитоактивной плазмы на металлической цилиндр, окруженный радиально неоднородным слоем плазмы. Внешнее магнитное поле параллельно оси цилиндра; волновой вектор падающей плоской волны перпендикулярен к этой оси. Плазма предполагается холодной и возмущения в ней описываются уравнениями Максвелла и двухжидкостными гидродинамическими уравнениями. Получены точные решения для полей для линейного и степенного профилей неоднородности плотности плазменного слоя. Сечения рассеяния вперед и назад как функция волнового вектора падающей волны получены для различных параметров задачи. Проанализированы зависимости этих сечений рассеяния от параметров задачи. Слой неоднородной плазмы увеличивает амплитуду колебаний сечения обратного рассеяния и изменяет в несколько раз величину сечения рассеяния вперед. У даній роботі розв’язано задачу дифракції низькочастотної електромагнітної хвилі, що падає з однорідної магнітоактивної плазми на металевий циліндр, оточений радіально неоднорідним шаром плазми. Зовнішнє магнітне поле є паралельним до вісі циліндра, хвильовий вектор падаючої плоскої хвилі - перпендикулярний до цієї вісі. Вважається, що плазма холодна, і збурення в ній описуються за допомогою рівнянь Максвела та двох рідинних гідродинамічних рівнянь. Отримано точні рішення для полів для лінійного і степеневого профілів неоднорідності плазмового шару. Для різних параметрів задачі одержано перерізи розсіяння вперед і назад як функція хвильового вектора падаючої хвилі. Проаналізовані залежності цих перерізів розсіяння від параметрів задачі. Шар неоднорідної плазми збільшує амплітуду коливань перетину зворотного розсіяння і змінює в декілька раз величину перетину розсіяння вперед.
Keywords: электромагнитная волна; дифракция; магнитоактивная плазма; неоднородная плазма; сечение рассеяния; electromagnetic wave; diffraction; magnetoactive plasma; non-uniform plasma; cross section